Short- and Long-Run Determinants of Mudharabah Deposit Growth: Evidence from Bank Muamalat Indonesia - Dea Rahmalia; Alvien Septian Haerisma; Sri Rokhlinasari (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2026)
This study aims to analyze the impact of the Profit-Sharing Rate, Capital Adequacy Ratio (CAR), and Third-Party Funds (DPK) on the growth of mudharabah deposits at Bank Muamalat Indonesia. The ARDL-ECM method is applied within this quantitative research to explore the inter-variable relationships more deeply. Through this framework, the study identifies both temporary short-term correlations and stable long-term relationships. The results indicate that, simultaneously, all three variables significantly influence the growth of mudharabah deposits. Partially, in the long run, all variables show a positive and significant effect, whereas in the short run, only DPK remains significant. These findings suggest that profit-sharing stability and capital strength play a crucial role in driving sustainable deposit growth, while short-term dynamics are more heavily influenced by fund-raising intensity. The novelty of this research lies in the use of the ARDL-ECM approach to detect differences in Sharia customer behavior toward banking indicators across two distinct timeframes.